Pinpointing disulfide connectivities in cysteine-rich proteins - Bernardino, K.; Pinto, M. E.F. [UNESP]; Bolzani, V. S. [UNESP]; De Moura, A. F.; Batista, J. M. (Royal Society of Chemistry (RSC), 2017)
A simple MD-based protocol is presented to accurately predict both the sequence and order of disulfide bond formation in proteins containing multiple cysteine residues. It provides a detailed description of their dynamical and structural features, which can be used to perform ensemble-Averaged ECD calculations. Plant cyclotides are used as model compounds.